Toward the use of CVD-grown MoS2 nanosheets as field-emission source - Deokar, Geetanjali; Rajput, Nitul S.; Li, Junjie; Deepak, Francis Leonard; Ou-Yang, Wei; Reckinger, Nicolas; Bittencourt, Carla; Colomer, Jean-Francois; Jouiad, Mustapha (Beilstein Journal of Nanotechnology, 2018)
Densely populated edge-terminated vertically aligned two-dimensional MoS2 nanosheets (NSs) with thicknesses ranging from 5 to 20 nm were directly synthesized on Mo films deposited on SiO2 by sulfurization. The quality of the obtained NSs was analyzed by scanning electron and transmission electron microscopy, and Raman and X-ray photoelectron spectroscopy. The as-grown NSs were then successfully transferred to the substrates using a wet chemical etching method. The transferred NSs sample showed excellent field-emission properties. A low turn-on field of 3.1 V/μm at a current density of 10 µA/cm2 was measured. The low turn-on field is attributed to the morphology of the NSs exhibiting vertically aligned sheets of MoS2 with sharp and exposed edges. Our findings show that the fabricated MoS2 NSs could have a great potential as robust high-performance electron-emitter material for various applications such as microelectronics and nanoelectronics, flat-panel displays and electron-microscopy emitter tips.
Keywords: chemical vapor deposition (CVD); field emission; molybdenum disulfide (MoS2); nanosheets; sulfurization; transmission electron microscopy (TEM)

(untitled) - Zhai, T.; Li, L.; Ma, Y.; Liao, M.; Wang, X.; Fang, X.; Yao, J.; Bando, Y.; Golberg, D. (Chem. Soc. Rev., 2011)

(untitled) - Zhang, H.; Tang, J.; Yuan, J.; Yamauchi, Y.; Suzuki, T. T.; Shinya, N.; Nakajima, K.; Qin, L.-C. (Nat. Nanotechnol., 2016)

(untitled) - Fan, S.; Chapline, M. G.; Franklin, N. R.; Tombler, T. W.; Cassell, A. M.; Dai, H. (Science, 1999)

(untitled) - Zhong, H.; Yang, G.; Song, H.; Liao, Q.; Cui, H.; Shen, P.; Wang, C.-X. (J. Phys. Chem. C, 2012)

(untitled) - Malesevic, A.; Kemps, R.; Vanhulsel, A.; Chowdhury, M. P.; Volodin, A.; Haesendonck, C. V. (J. Appl. Phys., 2008)

(untitled) - Viskadouros, G.; Zak, A.; Stylianakis, M.; Kymakis, E.; Tenne, R.; Stratakis, E. (Small, 2014)

(untitled) - Sachin, R. S.; Amit, S. P.; Mahendra, S. P.; Sandesh, R. J.; Mahendra, A. M.; Dattatray, J. L. (Mater. Res. Express, 2016)

(untitled) - Kashid, R. V.; Joag, P. D.; Thripuranthaka, M.; Rout, C. S.; Late, D. J.; More, M. A. (Nanomater. Nanotechnol., 2015)

(untitled) - Li, H.; Wu, H.; Yuan, S.; Qian, H. (Sci. Rep., 2016)

(untitled) - Palacios, E.; Park, S.; Butun, S.; Lauhon, L.; Aydin, K. (Appl. Phys. Lett., 2017)

(untitled) - Bo, Z.; Yang, Y.; Chen, J.; Yu, K.; Yan, J.; Cen, K. (Nanoscale, 2013)

(untitled) - Kashid, R. V.; Late, D. J.; Chou, S. S.; Huang, Y.-K.; De, M.; Joag, D. S.; More, M. A.; Dravid, V. P. (Small, 2013)

(untitled) - Li, Y. B.; Bando, Y.; Golberg, D. (Appl. Phys. Lett., 2003)

(untitled) - Devan, R. S.; Thakare, V. P.; Antad, V. V.; Chikate, P. R.; Khare, R. T.; More, M. A.; Dhayal, R. S.; Patil, S. I.; Ma, Y.-R.; Schmidt-Mende, L. (ACS Omega, 2017)

(untitled) - Deokar, G.; Vignaud, D.; Arenal, R.; Louette, P.; Colomer, J.-F. (Nanotechnology, 2016)

(untitled) - Eda, G.; Yamaguchi, H.; Voiry, D.; Fujita, T.; Chen, M.; Chhowalla, M. (Nano Lett., 2011)

(untitled) - Cho, S.-Y.; Kim, S. J.; Lee, Y.; Kim, J.-S.; Jung, W.-B.; Yoo, H.-W.; Kim, J.; Jung, H.-T. (ACS Nano, 2015)

(untitled) - Deokar, G.; Rajput, N. S.; Vancsó, P.; Ravaux, F.; Jouiad, M.; Vignaud, D.; Cecchet, F.; Colomer, J.-F. (Nanoscale, 2017)

(untitled) - Deokar, G.; Vancsó, P.; Arenal, R.; Ravaux, F.; Casanova-Cháfer, J.; Llobet, E.; Makarova, A.; Vyalikh, D.; Struzzi, C.; Lambin, P.; Jouiad, M.; Colomer, J.-F. (Adv. Mater. Interfaces, 2017)

(untitled) - Deokar, G.; Avila, J.; Razado-Colambo, I.; Codron, J.-L.; Boyaval, C.; Galopin, E.; Asensio, M.-C.; Vignaud, D. (Carbon, 2015)

(untitled) - Rajput, N. S.; Kim, S.-G.; Chou, J. B.; Abed, J.; Viegas, J.; Jouiad, M. (MRS Adv., 2016)

(untitled) - Lee, C.; Yan, H.; Brus, L. E.; Heinz, T. F.; Hone, J.; Ryu, S. (ACS Nano, 2010)

(untitled) - Kibsgaard, J.; Chen, Z.; Reinecke, B. N.; Jaramillo, T. F. (Nat. Mater., 2012)

(untitled) - Spevack, P. A.; McIntyre, N. S. (J. Phys. Chem., 1993)

(untitled) - Zhang, X.; Jia, F.; Yang, B.; Song, S. (J. Phys. Chem. C, 2017)

(untitled) - Zhang, Z.; Zou, L.; Aubry, C.; Jouiad, M.; Hao, Z. (J. Membr. Sci., 2016)

(untitled) - Kong, D.; Wang, H.; Cha, J. J.; Pasta, M.; Koski, K. J.; Yao, J.; Cui, Y. (Nano Lett., 2013)

(untitled) - Wu, Y.; Li, J.; Ye, J.; Song, Y.; Chen, X.; Huang, S.; Sun, Z.; Ou-Yang, W. (J. Alloys Compd., 2017)

(untitled) - Lee, S. Y.; Kim, U. J.; Chung, J.; Nam, H.; Jeong, H. Y.; Han, G. H.; Kim, H.; Oh, H. M.; Lee, H.; Kim, H.; Roh, Y.-G.; Kim, J.; et al. (ACS Nano, 2016)

(untitled) - Green, J. M.; Dong, L.; Gutu, T.; Jiao, J.; Conley, J. F., Jr; Ono, Y. (J. Appl. Phys., 2006)

(untitled) - Wang, F.-J.; Deng, L.-N.; Deng, J.-H. (Appl. Surf. Sci., 2015)

(untitled) - Xu, J.; Xu, P.; Ou-Yang, W.; Chen, X.; Guo, P.; Li, J.; Piao, X.; Wang, M.; Sun, Z. (Appl. Phys. Lett., 2015)

(untitled) - Fujii, S.; Honda, S.-i.; Machida, H.; Kawai, H.; Ishida, K.; Katayama, M.; Furuta, H.; Hirao, T.; Oura, K. (Appl. Phys. Lett., 2007)

(untitled) - Dwivedi, V. K.; Gopal, R.; Ahmad, S. (Microelectron. J., 2000)